Igor A. Fourmanov - Igor A. Fourmanov (National Research Mordova State University, 2020)
Introduction. Violence in social relations is an important humanitarian problem that concerns not only the behavior of individuals, but also the entire system of interaction within society as a whole. Most of the research in this area has focused on marital and family relations, leaving aside such essential areas of social life as war, the severity of criminal penalties, and the legality of the death penalty. The topic of studying students' attitudes to violence is relevant, since representatives of this age group belong to the most active and initiative part of modern society. The significance of this study is determined by the possible negative consequences of violent attitudes in behavior and social relations. Aggression and empathy as personality traits influence the formation and implementation of violent attitudes in behavior. The purpose of the article is to study students' violent attitudes. Materials and Methods. The study rests on the "Questionnaire of violent attitudes" by I. A. Fourmanov and M. V. Apanovich, "Aggression Questionnaire" (AQ) by A. Bass and M. Perry, "Interpersonal Reactivity Index" (IRI) M. Davis. The survey involved 731 first-fourth-year students of various Belarusian universities. Processing of the results was carried out using T-test for comparison of two independent samples, correlation analysis by Pearson and multivariate covariance analysis (MANOVA). Results. It was found that women have statistically higher rates of attitudes towards the war and punishing offenders than men. Men in comparison with women had more pronounced indices of attitudes towards corporal punishment of children and spousal violence. Discovered a positive relationship between indicators of physical and verbal aggression, anger, hostility, and negative relationship of decentration (PT), compassion (FS), empathic concern (EC) and personal distress (PD) with different attitudes towards violence in men and women. Physical aggression and hostility, regardless of gender, are significant factors that affect the strength of almost all violent attitudes. Characteristics of empathy influence forced installation variable depending on gender. Discussion and Conclusion. The results of the study demonstrate the current state of violent attitudes of modern students, and allow to develop a system of educational and training resources that promote the formation of students' peaceful, humanitarian and non-violent attitudes. This article will be useful to university teachers, scientists and psychologists.